ANALISIS KELAYAKAN FINANSIAL USAHA IKAN CAKALANG BEKU (KATSUWONUS PELAMIS) DAN IKAN DEMERSAL BEKU DI PULAU BEENG KABUPATEN KEPULAUAN SANGIHE - Sarapil, Costantein Imanuel; Kumaseh, Eunike Irene; Bawias, Ishak; Ikhtiagung, Ganjar Ndaru (Epigram, 2024)
The research aims to conduct a feasibility analysis of the frozen fish business in Beeng Village, Center South Tabukan District to improve the welfare of fishermen. In the feasibility analysis of frozen skipjack tuna business, the BCR value = 5.19. This means that the BCR value is> 1, so this indicator shows that the frozen skipjack tuna business is worth continuing. The NPV value is IDR 37.142.857,- which is positive and the IRR is 94%. This shows that the frozen skipjack tuna business is worth continuing. Meanwhile, in the feasibility analysis of the frozen demersal fish business, the BCR value was 16.43, NPV IDR 72.845.714, IRR 43%. BCR value > 1, NPV is positive, so this business is worth continuing.